104k views
2 votes
If tanA+sinA=m and tanA-sinA=n.prove that m^2-n^2=4√mn

1 Answer

1 vote

Let
a=\tan A and
b=\sin A. Then


m^2-n^2=(a+b)^2-(a-b)^2=(a^2+2ab+b^2)-(a^2-2ab+b^2)=4ab


\implies m^2-n^2=4\tan A\sin A

and


mn=(a+b)(a-b)=a^2-b^2


\implies4√(mn)=4√(\tan^2A-\sin^2A)

The expression under the square root can be rewritten as


\tan^2A-\sin^2A=(\sin^2A)/(\cos^2A)-\sin^2A=\sin^2A\left(\frac1{\cos^2A}-1\right)=\sin^2A(\sec^2A-1)

Recall that


\sin^2A+\cos^2A=1\implies\tan^2A+1=\sec^2A

so that


\tan^2A-\sin^2A=\sin^2A\tan^2A

and assuming
\sin A>0 and
\tan A>0, we end up with


4√(\tan^2A-\sin^2A)=4\tan A\sin A

so that


m^2-n^2=4√(mn)

as required.

User Wnnmaw
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.